Molecular characterization of carbapenemresistant Gram-negative bacilli clinical isolates in Algeria - Bourafa, N; Wafaa Chaalal; Bakour,S; Lalaoui, R; Boutefnouchet, N; Diene,S .D; Rolain, J-M. (My University, 2018)
Of the 68 GNB isolates, 13 (19%) showed reduced susceptibility to carbapenems, including, four Klebsiella pneumoniae, one Escherichia coli, six Acinetobacter baumannii, and two Pseudomonas aeruginosa. blaOXA-48 gene was detected in the five Enterobacteriaceae isolates, and blaOXA-23 was identified in all A. baumannii isolates. OprD mutations were revealed in the two P. aeruginosa isolates. A total of 11 out of the 13 carbapenem-resistant GNB were detected in inpatients, and the two remaining strains were isolated from outpatients. Molecular typing showed the presence of four sequence types (STs) among the OXA-48-producing K. pneumoniae isolates: ST101, ST147, ST163, and ST2017. ST533 was identified for the OXA-48 producing E. coli isolate. All of the A. baumannii and P. aeruginosa were assigned to the international clonal lineages ST2 and ST654, respectively